The dengue virus NS2B-NS3 protease retains the closed conformation in the complex with BPTI - Chen, Wan-Na; Loscha, Karin V.; Nitsche, Christoph; Graham, Bim; Otting, Gottfried (FEBS letters, 2014)
The C-terminal β-hairpin of NS2B (NS2Bc) in the dengue virus NS2B-NS3 protease is required for full enzymatic activity. In crystal structures without inhibitor and in the complex with bovine pancreatic trypsin inhibitor (BPTI), NS2Bc is displaced from the active site. In contrast, nuclear magnetic resonance (NMR) studies in solution only ever showed NS2Bc in the enzymatically active closed conformation. Here we demonstrate by pseudocontact shifts from a lanthanide tag that NS2Bc remains in the closed conformation also in the complex with BPTI. Therefore, the closed conformation is the best template for drug discovery.